Comparison of the core strength, balance ability and gait velocity between archers and sedentary individuals - Zulkifli, Erie Zuraidee; Zainuddin, Siti Hairuneesha; Ghafar, Rosniwati; Foong, Kiew Ooi; Chee, Keong Chen; Jiun, Sien Lau (Faculty of Sports Science and Recreation, 2025)
Sedentary lifestyle is a global problem. Although, many awareness campaigns have been carried out but the issue of physical inactivity still remained as a challange. Hence, more information is needed to increase the level of awareness among the sedentary population to change their lifestyle. Comparing quantitatively the most important features in their daily lives is an option. The objective of this research was to quantify the advantages of archery training to the body’s essential elements in performing daily activities which are core strength, balance ability and gait analysis. Thirty (n=30) young adults aged between 13 and 21 years old were recruited and assigned into archer and sedentary groups for this study. Comparisons were made between archer and sedentary groups for core strength, balance ability and gait analysis using curl-ups test, uni-pedal stance test and gait velocity. Results from this study showed that there were significant advantages by training archery regularly. Core strength test showed that the archer group were able to perform more average curl ups which is 34 repetitions per minute compared to 24 repetitions per minute by the sedentary group (p<0.05). Significant difference shown in balance ability in open eyes condition with a median result of 160.00 s for archer group while the sedentary group was 96.25 s (p<0.05). The archer group also had higher gait velocity compared to the sedentary group (p<0.05). Based on the results, sports training seems to provide better standing ability, stronger core and lower limb strength which will ease daily activities.